2016
DOI: 10.12968/ijtr.2016.23.3.123
|View full text |Cite
|
Sign up to set email alerts
|

Analogy learning in Parkinson's disease: A proof-of-concept study

Abstract: Background/Aims: Analogy learning is a motor learning strategy that uses biomechanical metaphors to chunk together explicit rules of a to-be-learned motor skill. This proof-of-concept study establishes the feasibility and potential benefits of analogy learning in enhancing stride length regulation in people with Parkinson's disease. Methods: Walking performance of thirteen individuals with Parkinson's disease was analysed using a Codamotion analysis system. An analogy instruction: ‘following footprints in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…It has been reported that the analogy should lead to the desired biomechanical movement and that preferably the analogy should contain a meaningful component to the participant 28,29 . Alongside the feasibility, also trends towards better walking performance after the analogy interventions were found, which demonstrate the potential of analogy learning in clinical practice 27,28 . However, to further establish the effectiveness of analogy learning in clinical gait rehabilitation, larger sample sizes and other research designs using a control condition are required.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…It has been reported that the analogy should lead to the desired biomechanical movement and that preferably the analogy should contain a meaningful component to the participant 28,29 . Alongside the feasibility, also trends towards better walking performance after the analogy interventions were found, which demonstrate the potential of analogy learning in clinical practice 27,28 . However, to further establish the effectiveness of analogy learning in clinical gait rehabilitation, larger sample sizes and other research designs using a control condition are required.…”
mentioning
confidence: 68%
“…Within the implicit condition the concept of analogy learning is the leading approach as it has shown to adopt characteristics of implicit motor learning 24,27,28 and provides therapists with a practical and feasible guideline to organise gait training. To choose and develop appropriate analogies, the same procedure as used in Kleynen et al, is followed 28 .…”
Section: Implicit Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this RCT an implicit and explicit motor learning walking intervention for people after stroke was evaluated. Based on scientific evidence [2,7,8,11] and expert experiences (practice based evidence) an intervention guideline was developed that outlined precisely how the treatments (implicit and explicit conditions) were supposed to be delivered. The guideline for both interventions was comparable in terms of dose (three sessions per week over a 3-week period) and intensity (30 minutes per session).…”
Section: Interventions Training Of Therapists and Assessorsmentioning
confidence: 99%
“…It can be a creative process as the analogy should reflect correct movement pattern and preferably be meaningful to the participant [7]. Examples of analogies to facilitate walking are reported ( Table 3), also a few other analogies to facilitate gait have been described by Kleynen et al [7] and Jie et al [8]. We hope that sharing the delivered analogies (Table 3) may function as a source of inspiration Tailored implicit and explicit motor learning walking interventions can be applied in a feasible manner to people after stroke who are in the chronic phase of recovery.…”
Section: Implications For Research and Clinical Practicementioning
confidence: 99%